ASCORBATE PEROXIDASE6 Protects Arabidopsis Desiccating and Germinating Seeds from Stress and Mediates Cross Talk between Reactive Oxygen Species, Abscisic Acid, and Auxin. Issue 1 (21st July 2014) - Chen, Changming; Letnik, Ilya; Hacham, Yael; Dobrev, Petre; Ben-Daniel, Bat-Hen; Vanková, Radomíra; Amir, Rachel; Miller, Gad
Abstract : An ascorbate peroxidase functions to protect maturing and early germinating seeds from stress and modulate the seed's cellular metabolism and signaling . Abstract: A seed's ability to properly germinate largely depends on its oxidative poise. The level of reactive oxygen species (ROS ) in Arabidopsis ( Arabidopsis thaliana ) is controlled by a large gene network, which includes the gene coding for the hydrogen peroxide-scavenging enzyme, cytosolic ASCORBATE PEROXIDASE6 (APX6), yet its specific function has remained unknown. In this study, we show that seeds lacking APX6 accumulate higher levels of ROS, exhibit increased oxidative damage, and display reduced germination on soil under control conditions and that these effects are further exacerbated under osmotic, salt, or heat stress. In addition, ripening APX6-deficient seeds exposed to heat stress displayed reduced germination vigor. This, together with the increased abundance of APX6 during late stages of maturation, indicates that APX6 activity is critical for the maturation-drying phase. Metabolic profiling revealed an altered activity of the tricarboxylic acid cycle, changes in amino acid levels, and elevated metabolism of abscisic acid (ABA ) and auxin in drying apx6 mutant seeds. Further germination assays showed an impaired response of the apx6 mutants to ABA and to indole-3-acetic acid. Relative suppression of abscisic acid insensitive3 ( ABI3 ) and ABI5 expression, two of the major ABA signaling downstream components controlling dormancy, suggested that an alternative signaling route inhibiting germination was activated. Thus, our study uncovered a new role for APX6, in protecting mature desiccating and germinating seeds from excessive oxidative damage, and suggested that APX6 modulate the ROS signal cross talk with hormone signals to properly execute the germination program in Arabidopsis.